Fishing as therapy: Impacts on job satisfaction and implications for fishery management. (1st June 2017) - Seara, Tarsila; Pollnac, Richard B.; Poggie, John J.; Garcia-Quijano, Carlos; Monnereau, Iris; Ruiz, Victor
Highlights: SE Puerto Rican and NE Region US fishermen's job satisfaction and well-being is compared. Data from Point Judith, RI 1977 is used for time comparison in US. Overall job satisfaction levels were high among both Puerto Rico and US fishermen. Puerto Rico and Point Judith 1977 presented the highest levels of job satisfaction. Changes in fishery management negatively affects job satisfaction among US fishermen.